2007
DOI: 10.1892/0891-6640(2007)21[1090:aoaplm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Point-of-Care Lactate Monitor in Emergency Admissions of Adult Horses to a Referral Hospital

Abstract: Background: Blood lactate concentration [LAC] is considered a useful indicator of disease severity in horses. Agreement of point-of-care (POC) lactate monitors with laboratory standards has not been established for clinically abnormal horses.Hypothesis: It was hypothesized that results from a POC lactate monitor would be in agreement with a laboratory-based measurement of [LAC].Animals: The study included adult horses presented for emergency evaluation.Methods: A prospective observational study was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…24,25 Urine creatinine concentration and GGT activity were measured (-24 and 24 hours) by use of an automated chemistry analyzer j with commercially available reagents and standards. Urine GGT (U/L)-to-creatinine (mmol/L) ratio was calculated.…”
Section: Administration Of Lps and Polymyxin B-mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Urine creatinine concentration and GGT activity were measured (-24 and 24 hours) by use of an automated chemistry analyzer j with commercially available reagents and standards. Urine GGT (U/L)-to-creatinine (mmol/L) ratio was calculated.…”
Section: Administration Of Lps and Polymyxin B-mentioning
confidence: 99%
“…Although a significant increase in neutrophil counts in the study reported here was detected in the polymyxin B group at 8 hours, compared with the control foals, significantly lower neutrophil counts were reported at 24 and 48 hours. Considering the time (8,24, and 48 hours) at which these differences were detected, it is likely that the differences in neutrophil counts were associated with varying degrees of rebound neutrophilia commonly observed after a severe neutropenic episode. 15,39 Thus, it is unlikely that polymyxin B administration had any clinically beneficial effect on the WBC or neutrophil count in this study.…”
Section: 33mentioning
confidence: 99%
“…It is particularly important to evaluate POC monitors in the population in which they will be used because underlying pathophysiology may introduce unexpected, and unmeasurable, bias. This problem was demonstrated in a recent study evaluating the performance of a POC lactate meter in which performance of the meter was different at PCV < 40% when compared with patients with PCV ≥ 40%, although PCV itself did not have significant impact on meter function when investigated singly 7 . Additionally, POC glucose monitors may perform differently at extremes of blood glucose concentration, such as reported in adult horses with acute abdominal disease, 6 than in the normal range.…”
mentioning
confidence: 99%
“…The lactate function has been validated for use in horses (Tennent-Brown and others 2007) while the triglyceride function has been validated for use in dogs and cats (Kluger and others 2010a, b). The device costs approximately £250 and each test around £2.40.…”
mentioning
confidence: 99%